EARNINGS QUALITY AND FINANCIAL PERFORMANCE OF LISTED SERVICE COMPANIES IN NIGERIA - Jafaru Musa, Maimuna; Gurama, Zakariyau; Ishiaku, Ahmed (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2023)
The study investigates the impact of earnings quality on the financial performance of listed Service Companies in Nigeria. It highlights the global importance of financial reporting quality, the significance of Nigeria’s service sector, and the unique features of Nigeria’s regulatory environment as justification for the research. The study used correlational research and data from annual reports of sampled companies from 2011 to 2020, employing various statistical analyses. The results indicate that earnings persistence significantly positively influences financial performance (ROA), while earnings predictability has a positive but not significant effect. Additionally, earnings smoothness significantly enhances financial performance. The study emphasizes the importance of maintaining earnings quality in financial reports, as stakeholders rely on this data for decision-making. It also suggests that policymakers enforce strict compliance with financial reporting regulations for listed service companies, given the significant impact of earnings quality on investment decisions. In summary, the study underscores the necessity of upholding and improving earnings quality for the success of the service sector in Nigeria and wealth maximization for shareholders.